2011
DOI: 10.1007/s10530-011-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the scale of marine bioinvasions in developing regions: a South African re-assessment

Abstract: As recently as 2009 the number of introductions recorded for South Africa comprised 22 marine and estuarine species. This review aims to reassess the diversity and scale of introduced marine and estuarine species in the region. Accurate taxonomic and systematic work, broad review of historical records and new sampling surveys across selected marine habitats conducted by a team of local and international experts has effectively revealed the presence of previously misidentified, overlooked, or new introductions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 61 publications
1
87
0
7
Order By: Relevance
“…This system supports the largest area of seagrass (some 350 ha) and highest macrofaunal biodiversity of any South African estuary (Turpie et al, 2002;Bandeira and Gell, 2003), with >100 macrobenthic species in its Zosterella capensis beds (Barnes and Ellwood, 2012), although almost 10% of these are on Mead et al's (2011) and other lists of introduced aliens. As seen in other estuaries (e.g.…”
Section: Study Sitesmentioning
confidence: 79%
“…This system supports the largest area of seagrass (some 350 ha) and highest macrofaunal biodiversity of any South African estuary (Turpie et al, 2002;Bandeira and Gell, 2003), with >100 macrobenthic species in its Zosterella capensis beds (Barnes and Ellwood, 2012), although almost 10% of these are on Mead et al's (2011) and other lists of introduced aliens. As seen in other estuaries (e.g.…”
Section: Study Sitesmentioning
confidence: 79%
“…Por esta razón, Cartlon (2009) ha propuesto que la cantidad de especies exóticas en sistemas que históricamente han sido considerados prístinos (e.g., costa sudafricana, costa argentina, costa chilena) se encontraría subestimada, y tras un análisis más profundo podría aumentar de 5 a 10 veces el número registrado. El ejemplo más emblemático lo constituye la costa sudafricana, en donde en primera instancia, se habían estimado 22 especies exóticas y 18 especies criptogénicas (Robinson et al, 2005;Griffiths et al, 2009), pero tras una exhaustiva revisión de registros históricos, análisis taxonómicos y muestreos en lugares poco estudiados, dichas cantidades se cuadriplicaron (Mead et al, 2011a(Mead et al, , 2011b.…”
Section: Discussionunclassified
“…In a recent re-assessment of the extent of marine bioinvasions in South Africa, Mead et al (2011) demonstrated that the number of introductions of marine and estuarine species in the region was four times greater than previously recorded. Through a combination of more exhaustive literature searches, taxonomic re-appraisal and targeted field work, they increased the number of recorded introductions from 22 (Griffiths et al 2009a) to 86, with a further 39 cryptogenic species, at the same time acknowledging that their assessment was still 'far from fully comprehensive' (Mead et al 2011(Mead et al , p. 1991.…”
mentioning
confidence: 91%